Magnetic Signatures of Ionospheric Disturbance Dynamo for CME and HSSWs Generated Storms - Waqar Younas; C. Amory‐Mazaudier; Majid Khan; M. Le Huy (Space Weather)
Abstract Ionospheric disturbance dynamo is one of the main processes that causes perturbations in the upper atmosphere during a magnetic storm. We present a new method, based on the least square fitting, for estimation of the magnetic signatures associated with ionospheric disturbance currents. Using a wavelet semblance analysis, the durations of disturbance dynamo electric fields have been investigated at three longitudinal sectors. For that we have analyzed the disturbance dynamo (Ddyn) for 19 magnetic storms. It has been found that during CME generated storms magnetic signature of Ddyn may be observed—depending on strength of the storm as well as on the duration of interplanetary magnetic field (IMF) Bz southward—in one, two or all three longitudes. The Oscillatory behavior of IMF Bz during the high‐speed solar wind streams (HSSWs) generates Ddyn globally and the corresponding effects are observed at all low latitude magnetic observatories. In this regard, the Joule heating estimation shows that CME and HSSWs generated storms have very different patterns. The Ddyn duration is found to be maximum for the storms occurring during equinox season. Moreover, the HSSWs events are more likely to cause—because of the oscillatory IMF Bz—long lasting Ddyn as compared to CME generated counterpart. This study presents a detailed analysis of disturbance dynamo as affected by longitudinal and seasonal variations. In this regard the difference in magnetic signatures, of CME and HSSWs originated storms, have been highlighted.